Aplikasi Formula Cair Pseudomonas fluorescens P60 untuk Menekan Penyakit Virus Cabai Merah - Loekas Soesanto; Endang Mugiastuti; Ruth Feti Rahayuniati (Jurnal Fitopatologi Indonesia, 2013)
Viral diseases of chilli pepper are difficult to control, therefore the use of Pseudomonas fluorescens P60 should be evaluated. The aims of this research were to determine the influence of liquid formula of P. fluorescens P60 on virod disease and on growth and yield of chili pepper. Randomized block design (RBD) experiment was composed of 7 treatments and 4 replicates, i.e., control, insecticide applicaton, P. fluorescens P60 application by seedling drenching and spraying for 1, 2, 3, 5, and 7 times. The result showed that 5 times application of P. fluorescens P60 by drenching and spraying was able to suppress viral disease and reduce disease intensity by to 73.37%, increasing density level of P. fluorescens P60 to 9.50 x 1011 and increase phenolic compounds (saponin, tannin and glycoside). The same treatment could increase plant height 23.7%, root lenght 6.44%, plant dry weight 66.68%, root dry weight 23.59%, and yield weight 53.16%.